Does the host's developmental stage affect host preference following an ovipositioning experience in Heterospilus prosopidis?. Issue 1 (21st September 2016) - Sasakawa, Kôji; Abe, Masato S.; Shimada, Masakazu
Abstract: Many parasitoid wasps exhibit 'oviposition learning, ' whereby females associate host‐related cues with oviposition and use them in subsequent searches for hosts. This is affected by various factors that have yet to be fully elucidated. We examined the effects of host developmental stage on oviposition learning in parasitoid wasps that utilize both larval and pupal hosts using Heterospilus prosopidis Viereck (Hymenoptera: Braconidae), an ectoparasitoid of Bruchinae beetles (Coleoptera: Chrysomelidae), as a model. First, we examined whether the induction of host species preference differs between oviposition on larval and pupal hosts. Oviposition choice experiments were performed for both larval and pupal hosts using two equally preferred host species – Callosobruchus chinensis (L.) and Callosobruchus maculatus (Fabricius) – and wasps that were conditioned by an oviposition experience on either of the two host species. We found an induction of host species preference in wasps conditioned with pupal hosts but not in wasps conditioned with larval hosts. Next, we examined whether the induced preference was host‐stage‐specific. Oviposition experiments with pupal‐host‐conditioned wasps and larval hosts as choice hosts indicated that learned cues were not used when searching for larval hosts. Similar results were obtained for larval‐host‐conditioned wasps. We compared oviposition behavior on larval and pupal hosts but found no behavioral differences that could contribute to the observed difference in host preference induction. Our results indicate that larval and pupal hosts have different effects on host preference following an oviposition experience in H . prosopidis, although the detailed mechanisms remain unclear. These findings are notable because in parasitoid wasps that utilize both larval and pupal hosts, host developmental stages have attracted little attention as factors affecting oviposition learning.